2019
DOI: 10.1001/jamanetworkopen.2019.9702
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Survival Rates After a Combination of Local Treatment and Systemic Therapy vs Systemic Therapy Alone for Treatment of Stage IV Non–Small Cell Lung Cancer

Abstract: Key Points Question Is there a survival benefit to combining local treatment and systemic therapy for stage IV non–small cell lung cancer? Findings In this comparative effectiveness research study, overall survival of patients with stage IV non–small cell lung cancer was superior for combination of systemic therapy with surgical resection or external beam radiotherapy/thermal ablation of the primary tumor site compared with systemic therapy alone. Effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 38 publications
0
20
0
2
Order By: Relevance
“…Prior studies have reported beneficial outcomes of multimodal therapy (combination of local and systemic therapy) [ 26 ]. In a study of NCDB data of patients with stage IV NSCLC, surgical resection plus systemic therapy or EBRT/thermal ablation plus systemic therapy was shown to be beneficial compared to systemic therapy alone [ 27 ]. Among the selected patients with limited metastases, benefits of local therapy in conjunction with systemic therapy have been observed [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported beneficial outcomes of multimodal therapy (combination of local and systemic therapy) [ 26 ]. In a study of NCDB data of patients with stage IV NSCLC, surgical resection plus systemic therapy or EBRT/thermal ablation plus systemic therapy was shown to be beneficial compared to systemic therapy alone [ 27 ]. Among the selected patients with limited metastases, benefits of local therapy in conjunction with systemic therapy have been observed [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Local therapy was independently associated with improved OS, particularly among patients without thoracic nodal disease or bone metastases, and with more than one metastatic site (54). In another retrospective study, OS benefit from the addition of local therapy was confined to T1-2, N0-1 squamous cell carcinoma patients with one metastasis (HR, 0.68; 95% CI, 0.57-0.80; P<0.001), whereas those with adenocarcinoma, T3-T4, N2-N3 and two or more metastases showed inferior OS compared to systemic therapy alone (55).…”
Section: Oligometastatic Diseasementioning
confidence: 99%
“…In particular, EBRT becomes an effective treatment option for a subset of patients who are not candidates for surgical resection. 81 Generally, for intraocular metastasis, systemic therapy seems to have a lower local disease control rate (DCR) and a higher local recurrence rate when compared with local treatment. Intervention using local treatments helps to achieve higher response rates, while possibly also increasing local treatment-related complications.…”
Section: Targeted Therapymentioning
confidence: 99%